Parents' Weekend/Homecoming football game. Photo 046 - Tobin, Joanie (Tufts Archival Research Center, 2008)
Parents' Weekend/Homecoming football game. Tufts lost to Trinity 7-0. Includes pre-game tailgating and Homecoming king/queen presentation.